2019
DOI: 10.3389/fpls.2019.00587
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Genotype, Growth Stage, and Mycosphaerella graminicola Strains on the Efficiency and Durability of Wheat-Induced Resistance by Paenibacillus sp. Strain B2

Abstract: Plant-growth-promoting rhizobacteria are known as potential biofertilizers and plant-resistance inducers. The current work aims to study the durability of the resistance induced as a response to the inoculation of wheat grains with Paenibacillus sp. strain B2 (PB2) and its influence by plant genotype, growth stage, and Mycosphaerella graminicola strain (the causal agent of Septoria tritici blotch or STB). The results of the plate-counting method showed that PB2 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…Many studies have demonstrated that plant genotype can affect the expression of induced resistance mediated by biological (Martinelli et al, 1993;Korolev et al, 2008;Banani et al, 2014;Alkooranee et al, 2015;Hossain and Sultana, 2015;Prashar and Vandenberg, 2017;Samain et al, 2019;Adam, 2020) and chemical (Herman et al, 2007;Ishikawa et al, 2007;Sharma et al, 2010Sharma et al, , 2012Walters et al, 2011;Cordova-Campos et al, 2012;Banani et al, 2014;Pawlowski et al, 2016) inducers in a wide variety of crops. Therefore, it is not surprising that like Tucci et al (2011), we observed genetic differences in ISR by Trichoderma against Botrytis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that plant genotype can affect the expression of induced resistance mediated by biological (Martinelli et al, 1993;Korolev et al, 2008;Banani et al, 2014;Alkooranee et al, 2015;Hossain and Sultana, 2015;Prashar and Vandenberg, 2017;Samain et al, 2019;Adam, 2020) and chemical (Herman et al, 2007;Ishikawa et al, 2007;Sharma et al, 2010Sharma et al, , 2012Walters et al, 2011;Cordova-Campos et al, 2012;Banani et al, 2014;Pawlowski et al, 2016) inducers in a wide variety of crops. Therefore, it is not surprising that like Tucci et al (2011), we observed genetic differences in ISR by Trichoderma against Botrytis.…”
Section: Discussionmentioning
confidence: 99%
“…According to additional field trials (data not shown), overall disease severity was higher in the greenhouse experiment than in field trials, suggesting that the artificial inoculation resulted in a disease pressure higher than that found in the field. It is possible that a higher inoculum than that found in the field was applied to the greenhouse experiment, since soil inoculum correlates with disease severity ( Lees et al, 2010 ) Furthermore, inoculum concentration correlation with disease severity is genotype dependent ( Alonso-Villaverde et al, 2011 ), and both the pathogen strain and the plant genotype influence host resistance in other phytopathogenic interactions ( Ors et al, 2018 ; Samain et al, 2019 ). These results suggest that a high disease pressure as applied in the greenhouse might negatively influence the resistance of Cheyenne and Lady Christl to black dot.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics and cytological analysis have been used to highlight pathogenesis related metabolites in several host-pathogen interactions, including interactions between S. tuberosum and microbial pathogens. Although recent studies showed the importance of the host variety and pathogen strain on quantitative resistance ( Ors et al, 2018 ; Samain et al, 2019 ), studies of plant-pathogen interactions often rely on the use of a model using a single susceptible and a single resistant genotype. Furthermore, the effect of the inoculation of C. coccodes on the metabolome of potato tubers has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paenibacillus sp. strain B2 was demonstrated to significantly reduce the symptoms caused by S. tritici by inducing an overexpression of different plant genes involved in defense and cell rescue [ 151 ]. In the same way, Petti et al (2010) [ 178 ] carried out one of the first transcriptomic analyses on barley to understand the impact of the Pseudomonas fluorescens strain MKB158 to protect from Fusarium head blight.…”
Section: Beneficial Bacteria Implicated In Plant Defensementioning
confidence: 99%